Larangan Kampanye Di Fasilitas Pendidikan Dalam Mewujudkan Pendidikan Politik Masyarakat: Telaah Yuridis Atas Putusan Mahkamah Konstitusi Nomor 65/PUU-XXI/2023 - R Haris Kurniawan; Paisol Burlian; Sutrisno Hadi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Education plays a strategic role in shaping citizens' political awareness through its educational, research, and community service functions. However, restrictions on election campaigns within universities, as stipulated in Law Number 7 of 2017 concerning General Elections, have sparked constitutional debate, particularly regarding the fulfillment of political rights and academic freedom. Constitutional Court Decision Number 65/PUU-XXI/2023 was issued in response to the judicial review of Article 280 paragraph (2) letter h of the Election Law, which prohibits campaigning in government facilities, including universities. This article aims to analyze the Constitutional Court's legal considerations in this decision and its implications for the role of universities as a means of public political education. This research uses a normative juridical method with a statutory and case approach. The results show that the Constitutional Court emphasized the importance of maintaining the neutrality of universities, while simultaneously opening space for academic, objective, and non-partisan political education activities. This decision strengthens the position of universities as a constitutional democratic learning space, while also defining the boundary between practical political campaigns and citizen political education.